Application of Theory of Planned Behavior in the Role of the Halal Value Exposure Model on Halal Purchase Behavior - Rif’ah Dwi Astuti; Andi - Setiawan; Sri - Wahyuni; Sugiyanta - Sugiyanta (Admisi dan Bisnis, 2022)
This study aims to determine the halal value exposure to halal purchase behavior, where digital marketing and perceived behavioral control have an important role. This study considers consumers who use halal beauty treatments and cosmetics. This study uses a structured questionnaire which was developed and distributed to 179 adolescent respondents in Central Java. The data were analyzed by applying structural equation modeling. The results showed that the halal value exposure model had a positive mediating effect on Halal Purchase Behavior. This study also confirms the active moderating role of the Theory of Planned Behavior scheme in digital marketing and perceived behavioral control of halal purchase behavior. Based on these findings, producers and distributors in the halal industry should maximize their sales by increasing the halal value of their products. Because consumers are smarter by considering the number of quality clues to make their choices on halal beauty care and cosmetics. Therefore, practitioners should consider the information to increase the demand for their products